Trends in Performance and Growth by Students With and Without Disabilities on Five State Summative Assessments. Issue 4 (2nd October 2018) - Buzick, Heather; Weeks, Jonathan
ABSTRACT: Indicators of student academic growth are desired in state accountability systems in order to approximate student learning over time and attribute observed growth to schooling inputs. Through an extant analysis of five states' assessment data, this study offers evidence about whether longitudinal match rates and measures of growth differ at the state level for students with disabilities, relative to students without disabilities. There were three main findings: 1) In states in which a modified assessment was offered, students with disabilities were more likely to have missing prior year scores, and consequently missing growth scores; 2) Low scoring students, many of whom had a disability, were more likely to have missing prior scores on the state general assessment, and consequently missing growth scores; 3) Students with and without disabilities showed similar growth using transition and gain score definitions of growth, but students with disabilities had lower growth when estimated via a regression-based model. Measurement and policy considerations are discussed.